Inhibitory effect of alendronate on bone resorption of autogenous free bone grafts in rats - (:unkn) unknown (W B SAUNDERS CO-ELSEVIER INC, 2007)
Purpose: This study was designed to investigate the effect of alendronate on the resorption of autogenous free bone grafts by biochemical and histopathologic methods. Alendronate is a potent inhibitor of osteoclast-mediated bone resorption with no adverse effect on the mineralization of bone. Materials and Methods: In this experimental study, 56 male Wistar rats were used. Autogenous free bone grafts were prepared with standard trephine bur in the right femur of each rat. The animals were then divided into 2 groups. In the first group, rats were treated with a daily subcutaneous injection of alendronate (0.25 mg/kg/day) for 2, 4, and 12 weeks, respectively. In the second group, rats were treated with saline solution injection for the same time periods. At the end of these periods, serum and overnight fasting urine samples were collected from all animals. In serum, the level of calcium, phosphate, parathyroid hormone, and 25 dihydroxyvitamin D were measured. In urine, pyridinoline, deoxypyridinoline, calcium, and creatinine were analyzed. The rats were sacrificed at 2, 4, and 12 weeks postsurgery. The number of osteoclasts and the number and size of resorptive lacunae were evaluated histopathologically. Results: Alendronate caused significant reduction in urinary pyridinoline, deoxypyridinoline levels biochemically, and the number of osteoclasts and resorptive lacunae histopathologically. Conclusion: Suppression of the graft resorption occurred in the alendronate-treated group. (C) 2007 American Association of Oral and Maxillofacial Surgeons.
Keywords: MUCOPERIOSTEAL FLAP SURGERY; POSTMENOPAUSAL OSTEOPOROSIS; BISPHOSPHONATE ALENDRONATE; BIOCHEMICAL MARKERS; ORAL ALENDRONATE; EXPERIMENTAL PERIODONTITIS; CANCELLOUS BONE; ROOT RESORPTION; MINERAL DENSITY; PAGETS-DISEASE